Formulasi Gel Ekstrak Etanol Daun Awar-awar dan Evaluasi Aktivitas Anti-inflamasi secara In Vitro - Khansa Nur Izzati; Gayatri Simanullang; Riri Fauziyya (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2025)
Gel is a semisolid dosage form that utilises a gelling agent, such as Carbopol 940, providing ease of application and efficient skin absorption. Ethanol extract of awar-awar (Ficus septica Burm. F) leaves, which contain flavonoids and tannins, has demonstrated promising anti-inflammatory potential. This study aimed to formulate and evaluate the stability of a gel containing the ethanol extract of awar-awar leaves, as well as assess its anti-inflammatory effects. The methods comprised phytochemical screening, gel formulation and evaluation, stability testing, and an in vitro anti-inflammatory assay. Four gel formulations were created: F0 (0%), F1 (1.5%), F2 (3%), and F3 (4.5%). Evaluation results showed that F0, F1, and F3 were homogeneous, with viscosities between 5,000-50,000 mPa·s, spreadability of 5-7 cm, and adhesion time exceeding 2 seconds, meeting Indonesian National Standard (SNI) requirements. However, pH testing during the cycling tests revealed instability in formulations F1 through F3 during storage. The anti-inflammatory test, conducted using the protein denaturation inhibition method, showed all three formulations had anti-inflammatory activity, with F3 being the most effective (92.20% inhibition). Therefore, F3 is considered the most promising formulation due to its high anti-inflammatory activity and acceptable pharmaceutical characteristics for gel preparations.